The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1093/nar/gkaa029
|View full text |Cite
|
Sign up to set email alerts
|

A crucial RNA-binding lysine residue in the Nab3 RRM domain undergoes SET1 and SET3-responsive methylation

Abstract: The Nrd1–Nab3–Sen1 (NNS) complex integrates molecular cues to direct termination of noncoding transcription in budding yeast. NNS is positively regulated by histone methylation as well as through Nrd1 binding to the initiating form of RNA PolII. These cues collaborate with Nrd1 and Nab3 binding to target RNA sequences in nascent transcripts through their RRM RNA recognition motifs. In this study, we identify nine lysine residues distributed amongst Nrd1, Nab3 and Sen1 that are methylated, suggesting novel mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…However, aside from the specific case of succinylation of histone proteins ( 22 ), succinylation of nuclear proteins has been detected in whole-cell lysates without information about their localization. The charge and modification state of lysine residues may affect the RNA interactions in canonical RNA binding or protein localizations ( 44 ). Succinylation inverts the charge of lysine residues and adds a bulky adduct, therefore imposing a significant functional impact ( 45 , 46 ) on the proteins.…”
Section: Resultsmentioning
confidence: 99%
“…However, aside from the specific case of succinylation of histone proteins ( 22 ), succinylation of nuclear proteins has been detected in whole-cell lysates without information about their localization. The charge and modification state of lysine residues may affect the RNA interactions in canonical RNA binding or protein localizations ( 44 ). Succinylation inverts the charge of lysine residues and adds a bulky adduct, therefore imposing a significant functional impact ( 45 , 46 ) on the proteins.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, it has been shown that several stress-responsive genes can be repressed by premature termination by the NNS-complex and alternative TSS usage under stress conditions allows excluding Nrd1 and Nab3 recognition sequences from the 5′ UTR and, thus, escaping NNS binding and transcription termination ( 55 ). In addition, several phosphorylation sites have been identified in Nrd1 ( 56 ) and very recently several methylation sites have been detected in both Nrd1 and Nab3 ( 57 ), but a role for these modifications in the regulation of transcription termination has not been demonstrated. The levels of the Sen1 protein have shown to be modulated during the cell cycle ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…PRM-MS can differentiate and relatively quantify peptides with isobaric post-translational modifications (PTMs). In yeast, in which the histone H3 K4 mono-methyltransferase SET1 was lacking, PRM-MS was used to quantify several newly identified methyl modifications ( Lee et al., 2020 ). Building a PRM-MS isolation list.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
“… (B) Relative total peak area of Nab3-K363me1 chromatographs in WT versus set1Δ , set2Δ , or set3Δ strains. Figure modified from Lee et al. (2020) .…”
Section: Quantification and Statistical Analysismentioning
confidence: 99%